Impairment of memory functions after acute head injury - Fodor, Iris E. (1972)
When memory functions are evaluated after head injury, two trends are apparent. Acute head injury patients with approximately normal intelligence demonstrate a reduced capacity to utilize structure in delayed recall relative to a control group. Furthermore, head injury patients with low intelligence demonstrate a wider memory deficit than the previous group, affecting perception and immediate recall as well. No relationship was found between severity of injury, recovery, and performance on the memory scale.